Acute Cholestatic Hepatitis Caused by Amoxicilin/Clavunate - Rosete, Marisa Isabel de Sousa Ferreira; Antunes, Joana; Gaudêncio, Margarida; Sousa, Fernando Ferraz e; Pereira, Amélia (Gazeta Médica, 2020)
A 65-year-old man was admitted to the emergency room, with a history of abdominal pain, choluria, fecal acholia, generalized pruritus and anorexia for four days. He indicated that it had been approximately 21 days since he had used amoxicillin/calvulanate for 7 days for tonsillitis and denied using any other medications. Laboratory data showed direct hyperbilirubinemia and elevated liver enzymes. Diagnostic investigation began with serological tests for virus, bacteria and auto-immunity which were negative. A liver biopsy was performed, and the pathology showed hepatocellular inflammation, cholestasis, and bile duct damage. Conclusion: The patient was diagnosed with cholestatic hepatitis associated with amoxicillin/clavulanate. He did not receive any specific treatment, only cholestyramine and ursodeoxycholic acid for pruritus.